Ethical Investment in Stock Screening and Zakat on Stocks - Rahman, Shafiqur (Journal of Islamic Finance, 2015)
Islamic finance is the fastest growing segment of the global financial system and has been experiencing an impressive double-digit growth in recent history. Following the growth trend of Islamic finance, a rapidly rising affluent and well-educated Muslim middle class from the Islamic world and Western countries is aspiring to match finance with faith and fueling demand for Islamic investments. This paper examines how Muslim investors can invest in the contemporary stock market in a way completely compatible with the letter and spirit of divine Islamic law or shariah, and how Islamic investment is considered for zakat—a religious obligation to donate to the poor and needy a certain percentage of wealth. The conditions laid down by shariah make Muslim investors’ participation in the stock market a special case of ethical investment. This paper discusses a qualitative screening process to identify stocks of companies that are engaged in business or activities permissible (halal) in Islam, and a quantitative screening process utilizing financial ratio analysis to allow companies in permissible business to use a tolerable level of interest-bearing securities and associated interest income and expenses. Stocks of companies passing these tests are designated as shariah-compliant stocks or halal investments and these stocks form the investment opportunity set for Muslim investors. The paper then focuses on how to cleanse investment income from shariah-compliant stocks contaminated by income from impermissible (haram) sources and concludes with a discussion of two opinions of Islamic jurists and shariah scholars on treatment of investment in stocks for zakat calculation.